HUBUNGAN PENGETAHUAN TENTANG TEKNIK MENYUSUI YANG BENAR DENGAN KEJADIAN PUTING SUSU LECET PADA IBU MENYUSUI DI KELURAHAN SUMAMPIR PURWOKERTO UTARA - Susilo Rini; Ikit Netra Wirakhmi (Universitas Harapan Bangsa Purwokerto, 2013)
Breastfeeding technique is one of the factors that affect milk production. If theincorrect feeding techniques, it can cause blisters and make the nipple breastfeedingmothers and babies rarely will affect subsequent milk production. Because milkproduction is strongly influenced by baby sucking at the breast. This study aims todetermine the relationship of the level of knowledge proper breastfeeding techniqueswith nipples rush incident in breastfeeding mothers at Teluk village, PurwokertoSelatan sub district, Banyumas District, 2013. This research is a correlation descriptive with cross sectional approach.Sampling Technique in this research uses total sampling. Sample of this research isNursing Mother 0-6 month who live at Teluk village, Purwokerto Selatan Sub Districtwith value 25 respondents. Collecting data using questionnaires.the type of data isthe primary data and data analysis using chi square, because the data in the form ofcategorical data (nominal and ordinal) with a maximum cell number 5 of the secondvariable. The majority of woman experience sore nipples that as many as 16 respondent(64%). Breastfeeding knowledge about proper breastfeeding techniques most havesufficient knowledge of the 14 respondents (56%). After analysis of data obtained bychi square p value < Î± that is 0,017 < 0,05 thus Ho is rejected and Ha isreceived.Can conclude that there was a significant relationship between knowledgeof proper breastfeeding techniquea with nipple rush in breastfeeding mothers Key words: knowledge of breastfeeding techniques, nipple rush.